Determinants of Postpartum Blues in Indonesia - Kurniawati, Dini; Septiyono, Eka Afdi (Universitas Airlangga, 2022)
Introduction: The condition of postpartum blues is difficult to detect as it is still considered an instinct from a mother. Postpartum blues is a psychiatric disorder that, if left untreated, causes severe mental problems. This study aims to determine the factors that influences postpartum blues in postpartum mothers.Methods: This study used a cross-sectional method. The population in this study were mothers who gave birth at Balung Hospital. The sample obtained were 330 mothers who gave birth from January to December 2019. The instrument used was a questionnaire consisting of the Edinburgh Postnatal Depression Scale, a family support questionnaire, and a questionnaire to determine the respondent's characteristic data (age, salary, education, employment, type of labor, husband support, pregnancy status, and risk of postpartum blues)Results: The results of the analysis using the chi-square found that the determinants of postpartum blues are age (p=0.002), salary (p=0.032), education (p=0.001), occupation (p=0.042), type of delivery (p=0.0001), husband's support (p=0.003), and pregnancy status (p=0.009) with p <0.05.Conclusion: Mothers who receive the related factors will feel that they are valuable and needed and therefore a sense of happiness and comfort will arise to improve the mother's mood. Health workers can support the factors that promote the reduction of the postpartum blues status.